The International Encyclopedia of Media Literacy 2019
DOI: 10.1002/9781118978238.ieml0233
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Media

Abstract: The use of media and technologies in education, for teaching and learning, has a long history whose development was particularly intense in the 20th century owing to the rapid spread of information and communication technologies, for example audiovisual media such as radio and television, digital media, and the Internet. The extensive use of educational technologies in teaching is reflected, first, in the birth of the movement for audiovisual instruction in the 1920s and, next, in the development between the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…L'uso del video in ambito educativo vanta una lunga e consolidata tradizione (Ranieri 2019; Rivoltella e Rossi 2019), che affonda le sue origini nella seconda metà del XIX secolo con i primi esempi di uso didattico del cinema negli Stati Uniti e in Europa, dove alcune scuole iniziarono a utilizzare la tecnica del filmstrip come supporto ai processi di insegnamento e apprendimento. All'epoca, l'uso educativo delle immagini fu accolto come una straordinaria opportunità per studenti e docenti, in quanto le immagini consentivano di avere una 'visione diretta' del mondo.…”
Section: Creditiunclassified
“…L'uso del video in ambito educativo vanta una lunga e consolidata tradizione (Ranieri 2019; Rivoltella e Rossi 2019), che affonda le sue origini nella seconda metà del XIX secolo con i primi esempi di uso didattico del cinema negli Stati Uniti e in Europa, dove alcune scuole iniziarono a utilizzare la tecnica del filmstrip come supporto ai processi di insegnamento e apprendimento. All'epoca, l'uso educativo delle immagini fu accolto come una straordinaria opportunità per studenti e docenti, in quanto le immagini consentivano di avere una 'visione diretta' del mondo.…”
Section: Creditiunclassified
“…A growing number of studies demonstrated how multimedia could positively impact learning when certain multimedia design principles were followed (Hyoung Jai Nusir et al, 2013;Ranieri, 2019). However, the impact of digital technologies on learning does not consist of improving learning in and of itself, but rather of shifting the individual's relationship with knowledge and information.…”
Section: Introductionmentioning
confidence: 99%